Safety culture at the workplace : A study on Malaysian manufacturers / Zuriah Abdul Rahman - Abdul Rahman, Zuriah (Universiti Teknologi MARA Cawangan Pahang, 2006)
Up to 1995 the International Labor Office reported that Malaysian manufacturers in general had a languid attitude towards safety at the workplace. The ILO office claimed that the majority of workplace injuries are attributed to attitude, knowledge and practices of employers as well as employees. After the tumultuous financial crisis of 1997, the contraction in economic growth from 1998 right up to 2002, SARS in 2003, the impact of the Iraq war in 2003-2004 and finally, the unprecedented tsunami tragedy at the end of 2004, Malaysia has undergone an eventful ten-year period, and this has especially affected the economic growth within the manufacturing sector. The lingering question is, “Has the safety culture in this sector improved during this period?” Records indicated a decline in the overall industrial accident rate and consequently the manufacturing sector as well. Research also confirmed this situation as the same direction is undertaken by management in general by putting heavy emphasis on the safety at the workplace. Safety Performance Index have improved and signs are showing a positive attitude by both management and employees on the seriousness of cutting down industrial accidents.